Influence of mental workload on professional identity of nursing students who were born between 1995 and 1999 (“95后”护生工作心理负荷对职业认同的影响) - LU Sheng (陆晟); WANG Zhenmeng (王振猛); SHENG Yuehong (盛月红) (中西医结合护理)
Objective To explore the influence of mental workload on professional identity of nursing students who were born between 1995 and 1999, in order to provide a basis for enhancing their sense of professional identity and provide advice to healthcare managers for decision-making. Methods A questionnaire-based survey using self-made general information scale, NASA Task Load Index for nurse, Nursing Profession Identity Questionnaire was conducted to nursing students who were born between 1995 and 1999 and participated in the internship in a grade A hospital in Shanghai. Results A total of 302 questionnaires were distributed, out of which 292 (96. 69%) were completed. The total score of NASA Task Load Index was (62. 33±18. 41), and the total score of nursing Profession Identity Questionnaire was (64. 14±10. 19). There was a negative correlation between mental workload and professional identity(P＜0. 01). Multiple regression analysis showed that occupation identity was influenced by multiple issues including place of residence、reasons of choosing the nursing specialty, degree of satisfaction with teacher and willingness to engage in nursing after graduation. Conclusion It is required to provide guidance and assistance for nursing students during the internship period and enhance their sense of accomplishment, in order to reduce the mental load and improve the professional identity of nursing students. (目的 探讨“95后”护生工作心理负荷对职业认同影响, 为提升其职业认同感提供依据, 为护理管理者决策提供相关建议。方法 采用一般资料问卷、护士版NASA任务负荷指数量表、护生职业认同问卷调查在上海市某三级甲等医院实习的“95后”护生。结果 共发放问卷302份, 回收有效问卷292份, 有效回收率96. 69%。“95后”护生心理负荷总分(62. 33±18. 41)分, 职业认同总分(64. 14±10. 19)分, 心理负荷与职业认同之间呈负相关关系(P＜0. 01); 多元回归分析显示, 家庭居住地、选择护理专业的原因、对带教老师是否满意和毕业后从事护理工作的意向等是“95后”护生职业认同的主要影响因素。结论 对护生在实习期进行正确引导, 提升护生的工作成就感, 给予护生更多的关心和帮助, 可以降低护生在实习期的心理负荷, 可以提高护生的职业认同度。)